Management of acute appendicitis in pregnancy (MAMA): Protocol for a multicentre observational study - Nilofer Husnoo; Ian Henderson; Hajra Khattak; Benjamin Rea; Catriona Wright; Brenda Narice; Jack Helliwell; Adil Rashid; Babu Karavadra; Sonia Lockwood; Arin Saha; Stephen Gerry; et al. (PLoS ONE, 2025)
Introduction Acute appendicitis is the most common emergency general surgical condition in pregnancy, affecting around 1 in 1000 pregnancies. Reaching a diagnosis is more challenging in this group because of altered clinical presentations and the limitations of diagnostic tools in pregnancy. There is limited guidance from national bodies in the UK on the management of this condition. This study aims to describe current diagnostic and treatment practices for acute appendicitis in pregnancy in the UK, and associated outcomes, to identify variations in practice and areas for improvement. Methods and analysis This is a UK-wide observational study. Hospitals providing an emergency general surgical service will be eligible to participate. The study consists of two components: (1) a site resource-profile questionnaire to assess the setup of services to care for the pregnant patient requiring emergency non-obstetric abdominal surgery to be completed by a senior collaborator at each participating site, and (2) a retrospective study of patients diagnosed with appendicitis or who had an appendicectomy for suspected appendicitis during a ten-year study period (2013–2023). Data will be collected on diagnostics, radiological findings, management approach and surgical and obstetric outcomes. The main measure of interest is the management approaches (operative versus non-operative; laparoscopic versus open surgery) and their association with selected outcomes. Multivariable logistic regression analyses will be conducted to identify factors which might predict the management strategy and outcomes. Ethics and dissemination The protocol for this service evaluation study has been reviewed by the University of Sheffield Research Ethics Committee. The study findings will be discussed in a multistakeholder workshop consisting of general surgeons, obstetricians and gynaecologists, radiologists, anaesthetists and patient representatives with a view to making recommendations for quality improvement work and further research. Key findings and recommendations will be disseminated through specialist societies.